(untitled) (Global Journal of Management and Business Research, 2015)
The South Asian Association for Regional Cooperation was officially established in December 08, 1985. The South Asian Free Trade Area (SAFTA) enter into force on July 01, 2006 under the umbrella of SAARC. From the same platform the SAARC Agreement on Trade in Services enter into force on November 29, 2012. SAARC Agreement on Promotion and Protection of Investment is yet to be finalized and enter into force. In the meantime 30 years gone. SAARC is the home of 21% (1.7 billion) world’s population with 9.12 % of global wealth. Combined SAARC is the third largest economy of the world. But a significant number of world’s poor people are living in this region. With its diverse landscape and variety of natural resources SAARC has every potential for economic development and poverty alleviation within shortest possible time. To achieve this objective SAARC leaders has to be committed for further economic integration under this common platform. Employment generation and entrepreneurship development could be an effective weapon in this regard. To generate employment for such a huge amount of population huge investment is needed. Intra SAARC investment promotion as well as attracting foreign direct investment (FDI) could be the one of the best options. SAARC Agreement on Promotion and Protection of Investment has to be enter into force as soon as possible. At the same time a central institution has to be established to promote FDI into the SAARC countries as per respective competitiveness, raw materials, skilled manpower etc. availability.